STRATEGI KOMUNIKASI POLITIK RAI MANTRA DAN JAYA NEGARA DALAM MEDIA SOSIAL INSTAGRAM PADA PEMILIHAN KEPALA DAERAH KOTA DENPASAR 2015 - Diah Desvi Arina, Ni Luh Putu; Amanda Gelgel, Ni Made Ras; Dewi Pascarani, Ni Nyoman (E-Jurnal Medium, 2018)
ABSTRACT Rai Mantra and Jaya Negara are candidates for Mayor and Vice Mayor of Denpasar in 2015 who take advantage of instagram during the campaign process. The purpose of this research is to know the political communication strategy of Rai Mantra and Jaya Negara on instagram at Denpasar Election 2015. This research used qualitative method with post-positivist paradigm. Data obtained from primary data and secondary data with the unit of analysis of this research is the communication strategy of candidate pair Rai Mantra and Jaya Negara and their team used in instagram. Data collection techniques were obtained through interviews, document studies and textual observation. Data analysis technique of this research consists of several components, data reduction, data presentation and conclusion. The result of this research is Political Communication Strategy of Rai Mantra and Jaya Negara in instagram at Denpasar Election 2015 done with three stages: segmentation, targeting, positioning. Segmentation is done at the beginning of its political communication strategy planning by mapping to enable their team and candidates to target their audiences, analyze audience behavior and create programs. Targeting is done by selecting the user segment of instagram of youth and the same age as the candidate. The third stage is the positioning done by uploading photos representing various community activities. Keywords: Denpasar Election 2015, Political Communication, Strategy, Social Media